Integration of Sharia Values in Notarial Practices in Muslim Wills - Julianti, Gili; Listyawati, Peni Rinda (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to examine the integration of sharia values in notarial practices in making wills for Muslim testators, with an emphasis on Article 939 of the Civil Code as the entry point for harmonization of national law and Islamic law. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that although Article 939 of the Civil Code regulates secret wills formally, its interpretation space allows notaries to consider the provisions of Islamic law, particularly in limiting parts of the will and determining the beneficiaries of the will according to the Compilation of Islamic Law. This integration is in line with the principles of maqāṣid al-syarī'ah and substantive justice, and strengthens the role of notaries in preventing inheritance disputes in the future.Keywords: Article 939 Of The Civil Code; Muslim Will; Notary; Sharia Values; Substantive Justice.